Sulfate‐reducing bacteria slow intestinal transit in a bismuth‐reversible fashion in mice. Issue 1 (31st July 2016) - Ritz, N. L.; Lin, D. M.; Wilson, M. R.; Barton, L. L.; Lin, H. C.
Abstract: Background: Hydrogen sulfide (H2 S) serves as a mammalian cell‐derived gaseous neurotransmitter. The intestines are exposed to a second source of this gas by sulfate‐reducing bacteria (SRB). Bismuth subsalicylate binds H2 S rendering it insoluble. The aim of this study was to test the hypothesis that SRB may slow intestinal transit in a bismuth‐reversible fashion. Methods: Eighty mice were randomized to five groups consisting of Live SRB, Killed SRB, SRB+Bismuth, Bismuth, and Saline. Desulfovibrio vulgaris, a common strain of SRB, was administered by gavage at the dose of 1.0 × 10 9 cells along with rhodamine, a fluorescent dye. Intestinal transit was measured 50 minutes after gavage by euthanizing the animals, removing the small intestine between the pyloric sphincter and the ileocecal valve and visualizing the distribution of rhodamine across the intestine using an imaging system (IVIS, Perkin‐Elmer). Intestinal transit (n=50) was compared using geometric center (1=minimal movement, 100=maximal movement). H2 S concentration (n=30) was also measured when small intestinal luminal content was allowed to generate this gas. Key Results: The Live SRB group had slower intestinal transit as represented by a geometric center score of 40.2 ± 5.7 when compared to Saline: 73.6 ± 5.7, Killed SRB: 77.9 ± 6.9, SRB+Bismuth: 81.0 ± 2.0, and Bismuth: 73.3 ± 4.2 ( P <.0001). Correspondingly, the Live SRB group had the highest luminal H2 S concentration of 4181.0 ± 968.0 ppb compared to 0 ± 0 ppb for the SRB+Bismuth group ( P <.0001). Conclusions & Inferences: Live SRB slow intestinal transit in a bismuth‐reversible fashion in mice. Our results demonstrate that intestinal transit is slowed by SRB and this effect could be abolished by H2 S‐binding bismuth. Abstract : Desulfovibrio vulgaris, common colonic sulfate‐reducing bacteria (SRB), slow small intestinal transit in mice. This slowing effect was not seen when the bacteria are heat‐killed suggesting that the slowing effect is dependent on metabolic activity of live SRB.